FAKTOR FAKTOR YANG MEMPENGARUHI AKSEPTOR DALAM MEMILIH ALAT KOTRASEPSI DI PMB DINCE SAFRINA - Brilian Dini Ma. Iballa; Widri Shabrina Hanum (LPPM Universitas Abdurrab, 2024)
Contraception is an attempt to prevent pregnancy. These efforts can be temporary, can also be permanent. Contraceptive use is one of the variables that affect fertility. The main objective of the family planning program is to fulfill people's demand for quality family planning and reproductive health services, reduce maternal mortality (MMR) and infant mortality (IMR), as well as address reproductive health problems in the framework of building quality small families. The purpo se of this study was to determine the factors that influence family planning acceptors in choosing contraception. This research is a quantitative analysis research with a cross sectional approach. Withdrawal of the number of samples with the accidental sam pling technique with a total of 40 respondents. From the results of the multivariate test, it was found that there was no effect on the level of education, knowledge, age and husband's support on the choice of contraception with a value (P > 0.1) which was not significant due to the lack of a sample in this study. It is recommended for further research to examine samples with a larger number and use a multivariate test .